Synthesis of photoluminescent carbon dots and its effect on chondrocytes for knee joint therapy applications - Rui Sun; Shichao Liu (Artificial Cells, Nanomedicine, and Biotechnology)
In the process of natural precursors examining for the carbon dots (CDs) synthesis, a bio-friendly and highly luminescent CDs synthesis is being reported herein. For the first time, we are reporting CDs synthesis using Selenicereus grandiflorus plant materials without any use of additional oxidizing agents like ethanol which was used in the earlier mentioned reports. Ultraviolet-visible spectroscopy (UV-Vis), X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, high-resolution transmission electron (HR-TEM) microscopy and Raman spectroscopy. This method is entirely safe to use in all biological practices because no toxic chemicals were used in this method. Further, we studied the toxicity of CDs against chondrocytes obtained from the knee joint. In order to inquire about the feasible harmful effects of exposing CD on the knee cells, we carried out CD treatment in SW-1353 chondrocytes. Cytotoxicity outcomes displayed a dosage-dependent reduction of cell viability. Therefore, we studied the toxic effects of CDs on the knee, indicating the important prospectives of CDs in future knee therapy.